Assessment of reproductive biomarkers in three‐spined stickleback (Gasterosteus aculeatus) from sewage effluent recipients. Issue 4 (7th June 2011) - Björkblom, Carina; Mustamäki, Noora; Olsson, Per‐Erik; Katsiadaki, Ioanna; Wiklund, Tom
Abstract The aim of this study was to examine the occurrence of endocrine disruption close to sewage treatment plant effluent discharges along the Finnish Baltic Sea coast using a set of reproductive biomarkers present in adult three‐spined stickleback (Gasterosteus aculeatus). Possible variation and sensitivity of the biomarkers during an entire reproductive period were also examined. The analysis of vitellogenin (VTG) for estrogenic activity and spiggin for androgenic activity, together with histopathological analysis indicated that sticklebacks were exposed to estrogenic loads sufficient to cause inappropriate production of VTG and to disrupt normal testicular structure in adult male sticklebacks. No androgenic disruption was observed. The results emphasize the need of a combination of several reproductive biomarkers in fish and repeated sampling for the detection of potential endocrine modulating substances under field condition. © 2011 Wiley Periodicals, Inc. Environ Toxicol, 2013.